MAIZE FARMERS' JOURNEY TO PROSPERITY: MARKET ACCESS IN MASINDI AND KIRYANDONGO DISTRICTS, UGANDA - Kato , Grace Nakato; John, Bosco Ouma (Ayden Journal of Management and Social Sciences, 2024)
The livelihood strategies of rural households encompass a diverse array of activities, including agriculture, agro-processing, trading, and off-farm pursuits, all aimed at meeting their essential needs for sustenance, income generation, and investment. As highlighted by the International Fund for Agricultural Development (IFAD) in 2003, agriculture remains a cornerstone of rural livelihoods, serving as both a source of food security and a means of income generation. However, rural households have increasingly diversified their economic activities, embracing off-farm strategies to enhance their resilience and economic well-being. The integration of rural households into market systems has emerged as a transformative force, catalyzing significant changes in their livelihood trajectories. Research by Oraboune (2008) underscores the positive impacts of market integration, including improved income earning opportunities, elevated standards of living, and a reduction in poverty levels among rural communities. By accessing broader markets for their agricultural produce and participating in value-added activities such as agro-processing and trading, rural households have been able to leverage market dynamics to their advantage. This abstract delves into the multifaceted nature of rural livelihoods, shedding light on the diverse strategies employed by rural households to sustain themselves and thrive in dynamic socio-economic environments. Drawing on insights from IFAD (2003) and Oraboune (2008), the abstract underscores the pivotal role of market integration in reshaping rural livelihoods and driving positive socio-economic outcomes. Understanding the complexities of rural livelihood dynamics is essential for policymakers, development practitioners, and stakeholders seeking to design effective interventions aimed at enhancing rural prosperity and resilience in the face of evolving market dynamics